2021
DOI: 10.3389/fphy.2021.727498
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Free-Standing Foils for Laser-Driven Particle Acceleration Experiments

Abstract: The recent development of petawatt-class laser systems sets a focus on the development of ultra-thin free-standing targets to access enhanced particle acceleration schemes vital for future applications, such as, medical and laser-driven nuclear physics. Specific strategies are required to improve the laser-to-particle energy conversion efficiency and increase the maximum particle energy. One of the promising approaches is based on the target design optimization; either by tuning key parameters which will stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent numerical and experimental studies have shown that creating nano- and microstructures, as well as patterns on the front surface of the targets, leads to an enhanced laser energy absorption and, hence, an improved conversion efficiency from laser energy into the resulting ion beam energy [ 21 ]. A number of surface structures have been proposed to this end, such as gratings [ 22 , 23 ], nanowires [ 24 ], nanobrushes [ 25 ], carbon foam [ 26 ], nanospheres [ 27 , 28 ] or nanoparticles [ 29 ]. When used as targets in high-power laser experiments, increasing the effective surface area of thin films through the use of specific growth methods can be an effective way of improving their laser energy absorption capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical and experimental studies have shown that creating nano- and microstructures, as well as patterns on the front surface of the targets, leads to an enhanced laser energy absorption and, hence, an improved conversion efficiency from laser energy into the resulting ion beam energy [ 21 ]. A number of surface structures have been proposed to this end, such as gratings [ 22 , 23 ], nanowires [ 24 ], nanobrushes [ 25 ], carbon foam [ 26 ], nanospheres [ 27 , 28 ] or nanoparticles [ 29 ]. When used as targets in high-power laser experiments, increasing the effective surface area of thin films through the use of specific growth methods can be an effective way of improving their laser energy absorption capabilities.…”
Section: Introductionmentioning
confidence: 99%